Improving Mathematical Critical Thinking and Habits Of Mind To Students in Elementary School - Nafiah, Maratun; MS, Zulela; Marini, Arita (JPI (Jurnal Pendidikan Indonesia), 2019)
This study aims to improve mathematical critical thinking and habits of mind through the application the RAVE-CCC (Read, Attend, Visualize, Estimate, Choice, Calculate, Check) strategy for six grade students of Elementary School. This study uses Classroom Action Research method. The research design used Kemmis and Mc Taggart's model. The research data were collected using field note techniques, interviews, observations, and mathematical critical thinking test  and habits of mind questionnaires. The results of this study indicate that, tests of students' mathematical critical thinking show increasing trend in each cycle. In the first cycle, the percentage of students who completed their scores with mathematical critical thinking skills was 70.83% which increases in the second cycle to 83.33%. The percentage of teachers and students activity in each cycle has increased. In the first cycle, the percentage of achievement indicators was 78.57%, in the second cycle, increased to 89.28%. The active participation of all students in the first cycle was 76.19% and in the second cycle increased to 87.5%. As for habits of mind, the percentage in the first cycle and second cycle also increased. In the first cycle the average percentage of students who showed a positive habits of mind was 66.66%, in the second cycle increased to 83.33%. Thus, it can be concluded that the adoption of the RAVE-CCC strategy can improve mathematical critical thinking and habits of mind.